SPE/IATMI Asia Pacific Oil &Amp; Gas Conference and Exhibition 2020
DOI: 10.2118/196341-ms
|View full text |Cite
|
Sign up to set email alerts
|

Successful Application of Novel Modified HF Acid System for Sandstone Matrix Acidizing in B Field

Abstract: Fines migration is the common formation damage mechanism in the sandstone reservoir of field B which has less established information on mineralogy distribution. There were many attempts to remediate the formation damage using conventional mud acid fluid system but resulted in mixed success rates. This situation warrant for the need for a modified acid recipe to avoid aggravation of fines migration problems in this field post acid treatment. This paper presents the pilot application of a modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Channa et al 162 acidized oil wells using 50 vol% GLDA solution and observed a 30 to 40% increase in productivity. Ting et al 163 used a chelating agent-based mud acid system to stimulate a reservoir of 49 °C (120 °F) and were able to increase production to approximately 200%.…”
Section: Field Applications Of Apcasmentioning
confidence: 99%
“…Channa et al 162 acidized oil wells using 50 vol% GLDA solution and observed a 30 to 40% increase in productivity. Ting et al 163 used a chelating agent-based mud acid system to stimulate a reservoir of 49 °C (120 °F) and were able to increase production to approximately 200%.…”
Section: Field Applications Of Apcasmentioning
confidence: 99%
“…Nowadays, the academy and industry have focused on developing new technologies to improve acid stimulation in sandstone formations to mitigate the critical issues associated with the high reactivity of the acid solutions. Most studies are focused on acid reformulation with chelating agents, solvents, and dispersants to increase the performance for fines removal . However, these new molecules increase costs, could lead to corrosion issues in the production system, and cause the formation of emulsions. One innovative alternative is the encapsulation of acid solutions, which shows a huge potential due to the increase in the acid penetration, the control over undesirable reactions, and the reduction of the corrosion issues without lowering the acid efficiency. …”
Section: Introductionmentioning
confidence: 99%
“…A chemical method of stimulation of oil and gas wells is the most mature and widely applicable method for acceleration of oil and gas production worldwide [1][2]. However, despite almost a century of experience in development of chemical methods for reservoir stimulation an industry still requires technology improvement [3][4][5][6][7]. Firstly, a reservoir stimulation technology improvement is always relevant, because of dynamics of oilfield development lifecycle [8][9].…”
Section: Introductionmentioning
confidence: 99%